2005
DOI: 10.1007/s10620-005-2917-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between NOD2/CARD15 Mutations and the Prevalence and Phenotypic Heterogeneity of Crohn’s Disease: Lessons from the Israeli Arab Crohn’s Disease Cohort

Abstract: The prevalence of Crohn's disease depends on geographic location and racial background. Arg702Trp, Gly908Arg, and Leu1007fsinsC mutations in the NOD2/CARD15 gene are associated with Crohn's disease in Caucasians. The mutation rate among Israeli Jewish patients is 27%-41%. The prevalence of Crohn's disease is much lower in the Israeli Arab compared to the Israeli Jewish population. We studied the NOD2/CARD15 mutation rate and disease phenotype (according to the Vienna classification) among the Israeli Arabs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
1
13
1
Order By: Relevance
“…Furthermore, we observed a high frequency of the R702W polymorphism in controls in comparison with patients and no statically significant differences were observed for the three main variants between patients and controls. This result is in harmony with other series (23)(24)(25)(26)(27) of Morocco, Tunisia, Turkey, South-Africa and Israeli Arab respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we observed a high frequency of the R702W polymorphism in controls in comparison with patients and no statically significant differences were observed for the three main variants between patients and controls. This result is in harmony with other series (23)(24)(25)(26)(27) of Morocco, Tunisia, Turkey, South-Africa and Israeli Arab respectively.…”
Section: Discussionsupporting
confidence: 89%
“…34 -36 Also, it is known that the CD prevalence is higher in North American Jewish people compared to Israeli Jews. 37 A positive association maintained after adjustment has also been found between CD and the cumulated incidence rates of 5 enteric reportable diseases. This result is opposite to what was found by Green et al 11 in Manitoba.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously found NOD2/CARD15 mutations to be rare in Arab Moslem CD patients and controls in contrast to the Israeli Jewish population, where these mutations are common [37]. The high frequency of NOD2/CARD15 mutations mainly among the Ashkenazi Jews may suggest that the mutations occurred after the migration of Jews from the Middle-East to Europe.…”
Section: Discussionmentioning
confidence: 92%
“…This may also explain the relatively low frequency of NOD2/ CARD15 mutations among the non-Ashkenazi Jews who came from the Mediterranean, North Africa, and Asia [30]. Previous studies showed a low rate of NOD2/ CARD15 mutations among populations with low prevalence and incidence of CD and vice versa [37]. We suggest that, in populations which are at low risk for CD (i.e., Arab Moslem) with a low frequency of NOD2 mutations, there are additional genes with a smaller effect that may play an important role in the susceptibility and pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 93%